Effects of Family Relations Towards Risk of Depression in Adolescents - Denisha Hawari; Margarita Maria Maramis; Subur Prajitno (Jurnal Psikiatri Surabaya, 2023)
AbstractIntroductions: In these days, with depression in adolescents levels getting higher in amounts, it should be assessed whether their relationships with their families have an effect on their risk of depression. This study aims to find out the effect of family relations on the risk of depression. Methods: Literature from PubMed that was published in 2015-2019 was searched using specific keywords. Then these literatures were filtered according to the inclusion and exclusion criteria of the variables used within the studies and then the results of the research were put in a table and the individual results are compared. Results: Four studies were conducted with similar independent and dependent variables to be then assessed and the results were that different family relations refer to different depressive tendencies. Conclusions: This study shows that there are effects to be had from family relations towards the risk of depression in adolescents.